ANALISIS AKTIVITAS KEUANGAN DAN PENGELOLAAN UTANG DALAM MENGUKUR KEMAMPUAN LABA PERUSAHAAN - Abdullah, Yunita Damayanti; Lamuda, Ilyas; Abdullah, Julie; Karundeng, Deby R. (Program Studi Akuntansi, 2023)
The purpose of this study is to analyze financial activity and debt management in measuring the company's profit capability (studies in the hotel industry listed on the Indonesian Stock Exchange). The purposive sampling method was used for sampling with analytical techniques using financial performance ratios and multiple linear regression analysis to analyze the effect of the independent variables on the dependent variable. The results showed that financial activity had a positive and significant effect on earning capacity, debt management had a non-significant positive effect on earning capacity, and simultaneously financial activity and debt management had a positive effect on earning capacity in hotel companies listed on the Indonesia Stock Exchange.